The Lack of an Empirical Rationale for a Revival of Discretionary Fiscal Policy - Taylor, John B (American Economic Review, 2009)
A decade ago in a paper, “Reassessing Discretionary Fiscal Policy,” published in the Journal of Economic Perspectives, I concluded that “in the current context of the US economy, it seems best to let fiscal policy have its main countercyclical impact through the automatic stabilizers. ... It would be appropriate in the current circumstances for discretionary fiscal policy to be saved explicitly for longer term issues, requiring less frequent changes.” This was not an unusual conclusion at the time. As Martin Eichenbaum (1997) put it, “There is now widespread agreement that countercyclical discretionary fiscal policy is neither desirable nor politically feasible,” or, according to Martin Feldstein (2002), “There is now widespread agreement in the economics profession that deliberate ‘countercyclical’ discretionary policy has not contributed to economic stability and may have actually been destabilizing in the past.” Despite this widespread agreement of a decade ago, there has recently been a dramatic revival of interest in discretionary fiscal policy. The purpose of this short paper is to review the empirical evidence during the past decade and determine whether it calls for such a revival. I find that it does not.